Evaluation of Different Fertilizers in Wheat Yields - D., Khishigsuren; J., Nambar; O., Sunjidmaa; Radnaabazar, Chinzorig (International Journal For Research In Agricultural And Food Science, 2020)
According to our survey results, yields in the range of 14.6 h/ha have been harvested after application of Darkhan-Rizo bacterial fertilizer. That is, it harvested yields in the range of 5 centner/ha higher than the control, and also it harvested yields in the range of 2.5 centner/ha more than the application of other types of fertilizers such as mineral fertilizers (granules) as well as 2.7 centner/ha higher than the application of organic fertilizer (originated from manure or dung of cattle) and 4.9 centner/ha more than the application of Humate-7B fertilizer, respectively.